Intracranial sclerosing extramedullary haematopoietic tumour mimicking meningioma in a patient with myelofibrosis: Case report. (June 2021) - Woodward, Zachary; Robertson, Thomas; Sim, Sarah; Tollesson, Gert
Highlights: SEMHT is a differential diagnosis in patients with myeloproliferative neoplasms. Early identification of SEMHT can allow for more informed treatment options. SEMHT misdiagnosis is common, it has been mistaken for carcinoma, sarcoma, & lymphoma. Abstract: Sclerosing extramedullary hematopoietic tumour is a rare tumour which can occur in certain myeloproliferative diseases, typically myelofibrosis. Typically these tumours present as a discrete retroperitoneal mass or masses, however they can occur in other sites within the body. In this case report we describe a 61-year old woman who underwent stealth guided bi-temporal craniotomy for resection of what was expected to be a large falx meningioma, however histopathology revealed the lesion to be a sclerosing extramedullary hematopoietic tumour. Following surgery, the patients post-operative recovery was complicated by intracerebral haemorrhage which required emergency evacuation and the patient remained in intensive care on a ventilator for 3 weeks. At one year follow up the patient reports her presenting symptoms of headaches, nausea, and vertigo had resolved.